2008
DOI: 10.1111/j.1530-0277.2008.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Cerebrospinal Fluid Tau Protein Levels in Wernicke’s Encephalopathy

Abstract: Intense neuronal cell death occurs transiently in WE, and the mechanism differs from that in AD. Neuronal damage is generally unaccompanied in WD. These results suggest that CSF total tau is a useful biological marker for WE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
1
18
0
3
Order By: Relevance
“…TD increases the activity of brain b-secretase and oxidative stress and exacerbates cerebral b-amyloid (Ab) deposition in APP/PS1 transgenic mice (Karuppagounder et al 2009;Zhang et al 2009). Furthermore, patients with Wernicke's encephalopathy induced by TD have been observed to have elevated phosphorylated Tau levels in their cerebrospinal fluid (CSF) (Matsushita et al 2008), which is also seen in AD patients. Thus, TD may contribute to the pathogenesis of AD.…”
Section: Introductionmentioning
confidence: 99%
“…TD increases the activity of brain b-secretase and oxidative stress and exacerbates cerebral b-amyloid (Ab) deposition in APP/PS1 transgenic mice (Karuppagounder et al 2009;Zhang et al 2009). Furthermore, patients with Wernicke's encephalopathy induced by TD have been observed to have elevated phosphorylated Tau levels in their cerebrospinal fluid (CSF) (Matsushita et al 2008), which is also seen in AD patients. Thus, TD may contribute to the pathogenesis of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Matsushita et al 6 describe a case series of acute WE in alcohol-dependent subjects and found elevated CSF tau level in all of them. The mean level of CSF tau was 1069 and the highest level found was 1995 ng/l.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, we have seen a rapid increase in the number of studies being published on CSF tau in Alzheimer's disease (AD)4 5 and other dementia syndromes 6. CSF tau has been proposed as a general marker for neuronal degeneration 7.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated values for CSF-tTau have also been found in a bovine variant of CJD [104]. Increases of CSF-tTau levels are observed in several other acute neurological conditions, such as severe malaria [105], Wernicke's encephalopathy [106], pediatric patients with brain tumor, hydrocephalus or serious CNS infections [107]. Studies assessing CSF-tTau in non-AD dementia such as FTD, PSP, CBD, Lewy body dementia (LBD), Parkinson's disease dementia (PDD) and amyotrophic lateral sclerosis (ALS) give contradictory results.…”
Section: Csf Total Tau: a Biomarker Of Neuronal Degenerationmentioning
confidence: 94%
“…The use of phosphodependent antibodies showed that pTau is recovered in the CSF and that several phosphoepitopes are present [98], [184] 192 AD 1 year 21% CV 21% CV NA NA [185] 29 AD 2 years 548 ± 355 577 ± 275 NA NA [186] 8 MCI 1 year 530 ± 450 560 ± 480 [146] 20 AD 3-8 years 568 ± 365 570 ± 435 NA NA [130] 53 AD 6 months 425 ± 30 431 ± 30 (6.1% CV) 93 ± 6 94 ± 6 (4.4% CV) [187] 50 AD 21 ± 8 months 731 ± 363 791 ± 419 84 ± 34 85 ± 35 [161] 22 MCI-AD 2.1 ± 0.5 years 750 ± 553 667 ± 327 49 ± 31 52 ± 29 [150] 12 MCI-AD 2 years 700 (240-1700) 710 (270 -1300) 86 86 (48-150) [156] 66 CJD 6 weeks tTau not significant tTau not significant NA NA [188] Transient increase in CSF-tTau and pTau levels in conditions with neuronal/axonal loss [190] Alcoholic dementia CSF-Tau/pTau significantly elevated in acute WE (n = 10) but not in chronic WE and after long-term follow-up [106] AD such as Thr181, Thr235, Ser396 and Ser404. A moderate to marked increase in CSF-pTau compared with controls has been found for all the different ELISA methods based on these antibodies [98,99].…”
Section: Csf-ptau: a Biomarker Of Hyperphosphorylationmentioning
confidence: 94%